PROFIL PEMAHAMAN KONSEP SISWA DITINJAU DARI TINGKAT KEMAMPUAN MATEMATIKA PADA MATERI FUNGSI KOMPOSISI - Gani, Fathurrahmah Abd.; Ismaimuza, Dasa; Sudarman, Sudarman (Universitas Tadulako, 2020)
Abstract: The aim of this research was to describe the profile of understanding the concept of class X MIA students based on the level of mathematical ability. The research was conducted at MA Alkhairaat Palu using a qualitative descriptive approach. The results of the study show that the understanding of the concept of ST in classifying the function of composition is that there is a function and operation of composition. Identify the characteristics of operations or concepts students use associative, distributive, composition operations and algebraic. Applying the concept students explain the properties and operations. Giving examples and not the composition function of the students explains the example, that there is an operation of composition and not there is no operation of the composition. Presenting the problem students presents in the form of mathematical models. Understanding the SS concept in classifying composition functions, namely a combination of functions associated with composition operations. Identify the characteristics of operations or concepts, namely the nature of distributive, operating composition and calculating algebra. Applying the concept students explain the properties and operations. Give an example and not an example of a composition function is an example is that there is a composition operation and not that there is no composition operation. Presenting problems in the form of mathematical models. Understanding the concept of SR in classifying the function of composition, namely there is a composition operation. Give an example and not an example of a composition function, is an example there is a composition operation and not an example, that is, there is no composition operation.